Diabetes in the context of dental treatment in an interdisciplinary approach - Julia Cabon; Julia Pejas; Anna Zawilska; Agata Trzcionka (Kazimierz Wielki University, 2023)
Instroduction:  Diabetes, including its numerous complications, is one of fundamental challenges of modern medicine. Over the years, many types of this disease have been appointed, differing in both etiological background and method of treatment. Dentists, when providing dental care to a patient burdened with diabetes, should pay special attention to the first symptoms reported by the patient as well as manifested in the oral cavity and surrounding tissues, e.g. in the form of xerostomia, hypertrophy of the salivary glands, changes on mucous membranes, impeded healing, or difficulties in combating local inflammation and infections, as well as in the form of physiological microflora disorders. Aim of the study: The aim of the study is to emphasize the need for controlling diabetes for the sake of general and oral health. Materials and methods: Our work is mainly based on the articles published in PubMed, websites or medical books. We were looking for keywords such as 'diabetes', 'dental treatment', 'symptoms of diabetes' or 'oral cavity diseases'. Results: Diabetes is often manifested by changes in the oral cavity, as evidenced by numerous scientific studies presented in the bibliography. Controlling the disease helps to eliminate lowering quality-of-life general symptoms and oral lesions. Conclusions: Faced with the challenges of modern medicine, the dentist is obliged to inform the patient about the diagnostic and therapeutic possibilities of both diabetes itself and its symptoms occurring in the oral cavity and then take all steps to ensure that the patient's condition is stabilised.